Portal vein pneumatosis. Report of a case and review of the literature - González Rull Tania; Medina Vega Francisco Antonio; Asz Sigall José (Instituto Nacional de Pediatría, 2014)
Portal venous gas is a condition usually detected in a radiologic sign in which gas is seen in the portal vein. We report the case of an infant with portal venous gas secondary to intestinal ischemia, which is one of the most frequent of its causes and which has a high mortality. This condition may be associated with many child- hood diseases. It is not necessarily fatal. Abdomen X-rays allows to diagnosis in advanced phases of the disease. However, ultra- sound and tomography have made it easier and more opportune to diagnose it. The treatment and the prognosis will depend on the cause of the portal venous gas. Treatment not always requires a surgery; prognosis is not always bad. Mortality increases when it is associated to intestinal ischemia.